Introducing multiple preference criteria in defeasible argumentation - Rotstein, Nicolás D. (2005)
In this research line we are exploring the possibility of having multiple preference criteria to compare arguments in in Defeasible Argumentation. In this work we are assuming a goaloriented Argumentative System, to which an application or an agent may seek an answer in response to a query. Thus, based on the current knowledge available, the system will decide whether there exists undefeated support for that query.